PROBLEMATIKA PENDIDIKAN ISLAM KONTEMPORER & SOLUSINYA - Musleh, Musleh; Wardi, Moh.; Hamid, Abdul (Reflektika, 2020)
The quality of a nation is largely determined by the role and quality of education used by that nation. A civilized society is an educated society. In this case, Muhammad Tidjani stated that education in Islam occupies an urgent and principled position and is something that every person who claims to be Muslim should not have. This article intends to describe various problems that occur in the education process nationally and seek solutions based on the perspective of educational figures and their thoughts.